Effects of extreme climate on agriculture in paddy field area in West Java Province (Indonesia) using multitemporal scenarios, GIS, and remote sensing - Riantini Virtriana; Tania Septi Anggraini; Kalingga Titon Nur Ihsan; Irwan Meilano; Dyah Ayu Retnowati; Agung Budi Harto; Albertus Deliar; Akhmad Riqqi; Anjar Dimara Sakti; Deni Suwardhi; Budhy Soeksmantono; Ketut Wikantika (Geomatics, Natural Hazards & Risk)
One of the factors of decreased productivity of rice fields is the agricultural hazards that occur in Indonesia due to climate and weather changes. One way to reduce the impact is by providing a need for information on areas affected by agricultural hazards so that it can be used for decision making in food security. This research conducts spatial modelling of agricultural hazards in rice fields integrates DEM, land cover, and precipitation data to determine flood and drought affected areas. This research calculates agriculture hazard using 4 different time scenarios: 5, 10, 25, and 50 years to obtain comprehensive agricultural hazards investigation and integrated based on two methods: expert judgment and frequency of occurrence in an area. The result shows, in the 2050 shows that the very high-class area from expert judgment and frequency of occurrence are 14131.23 and 11615.36 ha, respectively. This research is expected to identify areas that have agricultural hazards, especially in agricultural areas, and can be used for planning food security in the future.